Combining magnetic resonance imaging with readout and/or perturbation of neural activity in animal models: Advantages and pitfalls - Kosten, Lauren; Emmi, Serena Alexa; Missault, Stephan; Keliris, Georgios A. (Frontiers in Neuroscience, 2022)
One of the main challenges in brain research is to link all aspects of brain function: on a cellular, systemic, and functional level. Multimodal neuroimaging methodology provides a continuously evolving platform. Being able to combine calcium imaging, optogenetics, electrophysiology, chemogenetics and functional magnetic resonance imaging (fMRI) as part of the numerous efforts on brain functional mapping, we have a unique opportunity to better understand brain function. This review will focus on the developments in application of these tools within fMRI studies and highlight the challenges and choices neurosciences face when designing multimodal experiments.